Women in Management - Nagy, Beáta (Szociológiai Szemle, 2024)
This macro-level survey partly serves as a preliminary study to a project, entitled „Women in the Economy: The Managers”. In subsequent phases of research we will carry out interviews with women in powerful positions in the economy about their careers.